Facial pressure injuries and the COVID-19 pandemic: skin protection care to enhance staff safety in an acute hospital setting. (2nd March 2021) - Moore, Zena; McEvoy, Natalie L; Avsar, Pinar; McEvoy, Linda; Curley, Gerard; O'Connor, Tom; Budri, Aglecia; Nugent, Linda; Walsh, Simone; Bourke, Frank; Patton, Declan
Abstract : Objectives: The aim of this study was to determine the impact of a specially designed care bundle on the development of facial pressure injuries (PI) among frontline healthcare workers wearing personal protective equipment (PPE) during the COVID-19 pandemic. The primary outcome of interest was the incidence of facial PIs. The secondary outcomes of interest were facial pain while wearing PPE and ease of use of the care bundle. Methods: This study used a voluntary survey by questionnaire, supplemented by a qualitative analysis of interviews from a small purposive sample that took place in one large Irish hospital over a two-month period in 2020. The hospital was a city-based public university teaching hospital with 800 inpatient beds. The intervention was a care bundle consisting of skin protection, face mask selection, material use, skin inspection, cleansing and hydration developed in line with international best practice guidelines. All staff working in COVID-19 wards, intensive care units and the emergency department in the hospital were given a kitbag containing the elements of the care bundle plus an information pamphlet. Data were collected via a survey and interviews. Results: A total of 114 staff provided feedback on the use of the care bundle. Before using the care bundle 29% (n=33) of the respondents reported developing a facial PI, whereas after using the care bundle only 8% (n=9) of the respondents reported developing a facial PI. The odds ratio (OR) of skin injury development was 4.75 (95% confidence interval (CI): 2.15–10.49; p=0.0001), suggesting that after the care bundle was issued, those who responded to the survey were almost five times less likely to develop a skin injury. Interviews with 14 staff determined that the bundle was easy to use and safe. Conclusion: Among those who responded to the survey, the use of the bundle was associated with a reduction in the incidence of skin injury from 29% to 8%, and respondents found the bundle easy to use, safe and effective. As with evidence from the international literature, this study has identified that when skincare is prioritised, and a systematic preventative care bundle approach is adopted, there are clear benefits for the individuals involved.